Evaluation of the impact of an oncology urgent care clinic on preventable emergency department visits. Issue 28 (1st October 2022) - Russell, Brian; O'Donoghue, Ashley L.; Dechen, Tenzin; Lee, Emma M.; Sato-DiLorenzo, Aya; Stevens, Jennifer P.; Zerillo, Jessica Ann
Abstract : 338 Background: OP-35 is a publicly reported quality metric aimed at reducing preventable emergency department (ED) visits and hospitalizations in patients with cancer on chemotherapy. During the COVID-19 surge, one academic medical center opened the Respiratory Emergent Evaluation Service (REES) Unit, an urgent care clinic for patients with cancer and symptoms of COVID-19. In addition to preventing potential COVID-19 exposures in the clinic, this oncology-staffed urgent care evaluated patients who may have otherwise presented to the ED. We investigated the association between the REES urgent care clinic and patient ED evaluations for OP-35 diagnoses. Methods: This single center retrospective analysis included patients with cancer receiving infusion and oral chemotherapy who presented to the ED within 30 days of treatment. ED visits occurred between 1/2019-12/2021, including when the REES unit was open (3/2020-6/2021). Preventable ED visits were defined as having one of ten primary diagnoses, which have been identified by OP-35. Of these, COVID-related diagnoses included fever, pneumonia, sepsis, neutropenia and diarrhea. Interrupted time series analyses were utilized to investigate the association between the REES unit opening and preventable ED visits. Results: 3, 107 patients on chemotherapy were assessed in the ED from 1/2019-12/2021. Per week, there were 19.9 ED visits, 39.7% of which were for OP-35 diagnoses. When the REES unit opened, there was a 30% (95% CI -53% to -7%) reduction in preventable ED visits, corresponding to 2.62 (95% CI -4.61 to -0.63) fewer preventable ED evaluations per week. The primary driver of this reduction were presentations for COVID-related diagnoses, as there were 38% (95% CI -76% to -0.3%) fewer preventable ED visits weekly. During this period, there were approximately 6.9 patient visits per week to the REES unit. Conclusions: The introduction of an oncology urgent care clinic focusing on patients with symptoms of COVID-19 was associated with a reduction in potentially preventable ED visits. This analysis demonstrates the potential value of oncology urgent care clinics in reducing ED overcrowding and decreasing OP-35 related evaluations, which has patient experience, infection exposure and financial implications.Characteristics of patients who presented to the ED in the analysis period. Urgent Care Open Urgent Care Closed (3/2020 - 6/2021) (1/2019 - 3/2020) (6/2021 - 12/2021) Total visits, n 1, 166 1, 941 Age, y (IQR) 65 (55-73) 65 (57-73) Female, n (%) 619 (53%) 1, 028 (53%) Preventable ED visit, n (%) 440 (38%) 795 (41%) Pain 181 (16%) 320 (16%) Fever* 86 (7%) 163 (8%) Neutropenia* 45 (4%) 73 (4%) Pneumonia* 27 (2%) 55 (3%) Nausea 25 (2%) 46 (2%) Diarrhea* 23 (2%) 35 (2%) Sepsis* 19 (2%) 23 (1%) Anemia 17 (1%) 39 (2%) Dehydration 9 (1%) 29 (1%) Emesis 8 (1%) 12 (1%) Admitted, n (%) 875 (75%) 1, 419 (73%) *Diagnosis potentially related to COVID-19.